2022
DOI: 10.1155/2022/7934565
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Essential and Nonessential Fatty Acids of Irish Rapeseed Oils as an Indicator of Nutritional Quality

Abstract: The low saturated fatty acid content of rapeseed oil has resulted in it being classed as one of the most health-benefiting culinary oils. This study determines whether Irish rapeseed oils contain identical fatty acid profiles or whether distinct profiles exist between producers and producers’ successive oil batches. The fatty acid content of Irish rapeseed oils was determined in terms of the desirable MUFA and PUFA and saturated content of these oils. The fatty acid composition demonstrated significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Specific aldehydes are formed through lipid oxidation, hexanal is generated through oxidation of linoleic acid while octanal and nonanal, which are present in low amounts in rapeseed oils, are oleic acid derivatives ( Ivanova-Petropulos et al, 2015 ). Furthermore, it has been established that the Irish rapeseed oils tested here are abundant in linoleic acid and oleic acid which can justify the higher aldehyde content observed ( Coughlan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Specific aldehydes are formed through lipid oxidation, hexanal is generated through oxidation of linoleic acid while octanal and nonanal, which are present in low amounts in rapeseed oils, are oleic acid derivatives ( Ivanova-Petropulos et al, 2015 ). Furthermore, it has been established that the Irish rapeseed oils tested here are abundant in linoleic acid and oleic acid which can justify the higher aldehyde content observed ( Coughlan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 85%
“… Jing et al (2020) states that the roasted and nutty descriptors of rapeseed oils is derived from octanal, butanal and nonanal (via fatty acid degradation) which have high OAV resulting in the rapeseed possessing these sensory qualities ( Jing et al, 2020 ). Thus, the difference in “nuttiness” between the rapeseed oils may be attributed to the variations observed in the linolenic acid content of these oils ( Coughlan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapeseed oil is also known as canola oil or Brassica oil. Brassica is widespread in various conditions all over the world [ 6 ]. It is reported that Canada, Europe, and China are the leading producers of rapeseed oil in the world.…”
Section: Introductionmentioning
confidence: 99%